A Comparison of the Efficacy and Safety Between Hyaluronic Acid and Polylactic Acid Filler Injection in Penile Augmentation: A Multicenter, Patient/Evaluator-Blinded, Randomized Trial. Issue 4 (1st March 2019) - Yang, Dae Yul; Ko, Kyungtae; Lee, Seong Ho; Lee, Won Ki
ABSTRACT: Background: Studies about the clinical utility of fillers on penile augmentation (PA) are lacking. Furthermore, no randomized study has compared the utilities of fillers. Aim: To compare the efficacy and safety between hyaluronic acid (HA) and polylactic acid (PLA) filler injection for PA. Methods: This prospective, randomized patient/evaluator-blind, comparative multicenter study consisted of an initial 2-week baseline period and 48-week patient/evaluator-blind post-injection period. 72 patients with small penis syndrome were enrolled from 3 institutions between March–July 2016. Patients were divided into 2 groups: the HA group, comprising 36 patients injected with HA, and the PLA group, comprising 36 patients injected with PLA. Main Outcome Measures: Penile girth and satisfaction were assessed at baseline and at 4, 12, 24, and 48 weeks after injection. Results: Penile girth increases adequately lasted ≤48 weeks in both groups (16.95 ± 10.53 and 13.49 ± 9.98 mm of mean increase in the HA and PLA groups, respectively; P < .001). The mean penile girth increase in the HA group was significantly greater than that in the PLA group at 4 weeks ( P < .001). Subsequently, it gradually decreased and was no longer significantly different at 48 weeks ( P  = .075). Satisfaction levels increased after injection and were maintained ≤48 weeks. No significant differences were observed in the overall satisfaction level between the groups ( P > .05). Filler injection–related adverse events were mild and transient and occurred in 1 and 3 patients in the HA and PLA groups, respectively. Clinical Implications: This study provides an overview of the efficacy and safety of HA and PLA fillers, which are the most commonly used soft tissue fillers for PA. Strength and Limitations: This study, to our knowledge, is the first to compare the efficacy and safety between different filler injections for human PA. However, it was impossible to perform a researcher-blinded trial because of the unique properties of fillers, and 31 patients (43.1%) were dropped during the study period. Conclusions: Both HA and PLA filler injections for PA led to a significant augmentative effect without serious adverse events and had clinically comparable efficacy and safety.